Repression And Sublimation In Forrest Gump By Winston Groom: A Psychoanalytic Investigation - Friscilla, Okti Dea; Antaridha, Rabbi (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2025)
This study examines the main character, Forrest Gump, from Winston Groom’s 1986 novel. Despite being labeled an "idiot" and facing ridicule, Forrest achieves remarkable success. The research focuses on two key questions: how repression and sublimation are expressed in the novel. Using Sigmund Freud’s theories on defense mechanisms, the study explores Forrest’s psychological struggles and achievements. Freud’s concepts of consciousness (conscious, preconscious, and unconscious) and the structural model (id, ego, and superego) provide the framework for analyzing Forrest’s repression and sublimation. The research employs qualitative methods, including close reading of the novel, to collect and analyze data. Findings reveal that Forrest’s self-defense mechanisms manifest through his ability to overcome societal judgment and achieve greatness, highlighting the complexity of his character despite his perceived limitations. This study underscores the interplay between psychological defense mechanisms and personal success, offering a deeper understanding of Forrest Gump’s resilience and accomplishments.